2018
DOI: 10.1155/2018/4740739
|View full text |Cite
|
Sign up to set email alerts
|

Gengnianchun Extends the Lifespan of Caenorhabditis elegans via the Insulin/IGF‐1 Signalling Pathway

Abstract: Gengnianchun (GNC), a traditional Chinese medicine (TCM), is believed to have beneficial effects on ageing-related diseases, such as antioxidant properties and effects against Aβ-induced toxicity. We previously found that GNC extended the lifespan of Caenorhabditis elegans. However, the mechanism underlying this effect was unclear. In this study, we further explored the mechanisms of GNC using a C. elegans model. GNC significantly increased the lifespan of C. elegans and enhanced oxidative and thermal stress r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…Insulin/IGF-1-like signaling is considered to be the first pathway to regulate lifespan of C. elegans (Meng & Li, 2018). In addition, it plays important roles in stress resistance, metabolism, and reproduction (Lee et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin/IGF-1-like signaling is considered to be the first pathway to regulate lifespan of C. elegans (Meng & Li, 2018). In addition, it plays important roles in stress resistance, metabolism, and reproduction (Lee et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Many plants or plant derivatives such as green tea [31], tomatidine [32], Streblus asper [33], Paullinia cupana [34], Gengnianchun [35], and mulberry [36] were observed to extend lifespan and healthspan along with improving stress response and antioxidant mechanism in C. elegans. The present study tries to understand the effect of C. nervosum in extending lifespan and healthspan, incorporating neuroprotection along with improving stress resistance in C. elegans .…”
Section: Introductionmentioning
confidence: 99%
“… R04A9.7 3565956 The traditional Chinese medicine Gengnianchun (GNC) prolongs the lifespan of C. elegans . Comparison of genome-wide transcriptional profiling of untreated and GNC treated worms at day 22 showed that GNC downregulated the expression of R04A9.7 [ 60 ]. Gene symbol NCBI gene ID Ageing relevance evidence rbx-1 179358 RNAi of rbx-1 results terminal stage arrest during embryogenesis[ 61 ].…”
Section: Resultsmentioning
confidence: 99%